Research Methods for the Social Sciences. - Wellington, Jerry (Continuum International Pub. Group, 2007)
The aim of this book is to provide an introductory but not simplistic guide to research in the social and behavioural sciences. The book sets out to tackle difficult issues and concepts in a scholarly but accessible manner, providing ample guidance and signposts to further reading. We explore a wide range of questions about research and research methods, including:. * What counts as 'good research'?. * Research approaches, paradigms, methods and methodology: what are they and what is the difference?. * What is the so-called 'qualitative/ quantitative'?. * When and where is quantitative researc.